PENINGKATAN PENGELOLAAN PENJUALAN MELALUI PELATIHAN PEMBUKUAN SEDERHANA DAN PELAPORAN KEUANGAN DI DESA GENTANSARI KECAMATAN PAGEDONGAN, KABUPATEN BANJARNEGARA - Ainiyah, Ghonimah Zumroatun; Rudianti, Walid; Yubiharto, Yubiharto; Permatasari, Kartika Dewi (STIE Pelita Nusantara, 2022)
The residents of UMKM business actors in Gentansari Village, Pagedongan District, Banjarnegara Regency experience various problems, namely the lack of understanding of these UMKM entrepreneurs regarding the importance of packaging and labeling on a product, which can add a competitive advantage to business actors compared to their competitors and the importance of good financial reporting records for business actors. increase sales turnover, and understand that in the digital era there are many applications to help record financial statements. the importance of product packaging and labeling from 50% to 100%. All snack food UMKM actors understand how to further improve their ability to innovate in packaging and labeling marketed products to make them more attractive, so that the goal of attracting buyers' attention can be achieved. And of course it can have a positive impact on increasing the income of the community. Second, the socialization of the recording of financial reporting has met the targeted output, namely an increase in understanding of the importance of recording financial reporting.Keywords: packaging, financial report recording